EFFECTS OF FERMENTATION LENGTH ON CHEMICAL COMPOSITIONS, ORGANIC ACIDS, FATTY ACID PROFILES, AND RUMINAL DEGRADATION OF FERMENTED CONCENTRATE USING TAMANU KERNEL CAKE - Dimas Hand Vidya Paradhipta; Aisha Nadia Firuza; Innaya Sekar Amanullah; Cuk Tri Noviandi; Ali Agus; Chusnul Hanim; Aziz Umroni; Sinta Maharani (Journal of Animal and Plant Sciences, 2026)
This study investigated the effects of fermentation length on the chemical compositions, fatty acid profiles, organic acid production, and aerobic stability of fermented concentrate. Concentrate used tamanu kernel cake (TKC), serving as a source of protein and unsaturated fatty acids, combined with dried cassava, wheat pollard, soybean meal, and molasses. The concentrate before fermentation contained 19% crude protein (CP), and 36% neutral detergent fiber. Concentrate was fermented for 3, 7, 14, 21, and 60 days in quadruplicate. Longer fermentation time led to a linear increase in the loss of dry matter (DM) (P=0.004), organic matter (P=0.033), and CP (P=0.002) of fermented concentrate. Longer fermentation time caused a linear decrease in pH (P<0.010), but increased ammonia-N (P=0.006), lactate (P<0.001), acetate (P<0.045), and lactic acid bacteria (LAB) count (P<0.001). The 60 days treatment led to higher ammonia-N (P=0.003), lactate (P<0.001), acetate (P<0.001), and LAB count (P<0.001) compared to 0 to 7 days. Yeast (P<0.001) and bacillus (P<0.001) counts showed a quadratic pattern, where their counts at 60 days decreased lower than 3 days (P<0.001). Total fatty acid decreased linearly (P<0.001) with longer fermentation time, but each fatty acid profile remained unaffected. Aerobic stability was higher (P<0.001) at 21 and 60 days of fermentation compared to other durations. Fermentation at 3 and 7 days increased (P<0.010) the total degradable fraction in the rumen. In conclusion, fermenting concentrate based on TKC for 21 days increased aerobic stability and fermentation quality with less losses of nutrients and fatty acids, while fermenting for 3-7 days increased in vitro fermentability.
Keywords: Fermented concentrate; Fatty acid profile; Fermentation length; Ruminal degradation; Tamanu kernel cake